VALUE-BASED REPUTATION: TRANSFORMING ISLAMIC BANKING GOVERNANCE IN REALIZING THE SUSTAINABLE DEVELOPMENT GOALS (SDGs) - Abdul Hafith; Baiq El Badriati; Riduan Mas’ud (PT. Jurnal Center Indonesia Publisher, 2025)
This study aims to construct a conceptual model integrating value-based governance, value-based reputation, and the Sustainable Development Goals (SDGs) within the context of global Islamic banking. The research is motivated by the need to bridge Islamic ethical values with modern governance and sustainability paradigms that emphasize the balance between profitability, moral integrity, and social responsibility. Employing a systematic literature review and thematic synthesis through qualitative analysis, this study identifies, categorizes, and synthesizes key conceptual themes relevant to the research focus. The findings reveal that value-based governance serves as an ethical foundation that strengthens value-based reputation, while the latter functions as a catalyst for achieving sustainable development objectives. The synergy among these three elements produces a governance model that positions the principles of maqāṣid al-sharī‘ah as a normative framework for ethical, transparent, and sustainable Islamic financial practices. The primary contribution of this research lies in the simultaneous integration of the three major frameworks—value-based governance, value-based reputation, and SDGs—which enriches theoretical discourse on Islamic financial governance and provides strategic direction for the development of policy, sharia auditing, and sustainability reporting systems oriented toward ethical values and global welfare.